Ensuring security framework for WBANs. (3rd April 2021) - Pathak, Vinay; Singh, Karan; Aggarwal, Sudhanshu; Dhoot, Anshita
Abstract: Wireless body area(WBANs) network is a new technological development that is capable to monitor and process human health remotely. In this process, the wearable wireless sensor plays a vital role in the collection of information. As the information collected by wearable wireless sensors are very critical security is necessary which can able to take care of security and reliability at the same time. Reliability is necessary to build trust between endusers. Nowadays instead of physical attack new type of cyber attack will take place on the digital information. Due to the new type of attack in the cyber world special type of secure model needed to fulfil the current need. The proposes a secure and efficient authentication and privacy mechanism (SEAPM), which shows a better result in comparison to the existing algorithm in their previous works. This work includes a mechanism which needs less resource comparatively. Only authentic entities can able to interact with the authentic server which essential requisite for both sides.